Breastfeeding Practices among Urban Mothers of Central Kerala, India: A Cross-Sectional Study - Fathimathusalma Othayoth; Prabhakumari Chellamma; Sajna Mathumkunnath Vijayan; Jackson Kulampallil Sebastian; Rini Raveendran (Journal of Community Health Research)
Background: The practice of breastfeeding is vital in child nutrition and morbidity. The authors aimed to determine breastfeeding practices and factors related to Exclusive Breastfeeding (EBF) among mothers with children aged six months to 2 years in an urban area of Thrissur district, Kerala, India. Methods: This was a community-based and cross-sectional study conducted on 339 mothers using cluster sampling in 2016 for one year in the urban area of Thrissur district, Kerala. Details regarding sociodemographic factors, obstetric history, child-related data and breastfeeding practices were collected from mothers using a pretested and semi-structured questionnaire. Analyses were done using SPSS16 and Epi Info 7. Results: The mean age of study population was 27.21 ± 4.27. 223 mothers (65.78 %, 95% CI = 60.43-70.77) initiated breastfeeding within 1 hour, and prelacteal feeding was observed in 25 cases (7.37%, 95% CI = 4.92-10.83). 99.71% practiced feeding on demand, and 30.97% (95% CI = 26.15- 36.24) of children were exclusively breastfed up to 6 months with mean duration of 3.95± 1.79 months. The mean age at which complementary feeding started was 4.83 ± 1.32 months. Cultural beliefs, mothers' employment, and problems during breastfeeding were significant predictors of EBF for up to 6months. Conclusion: Despite high educational status and good antenatal care among the study population, breastfeeding practices were not carried out at the recommended level. Breastfeeding was initiated within 1 hour of delivery by 2/3rd ,and  1/3rd of the children were exclusively breastfed up to 6 months. Cultural beliefs and mothers' employment were factors associated with EBF.